1993
DOI: 10.1083/jcb.121.1.179
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization and tissue distribution of the A and B variants of the integrin alpha 6 subunit.

Abstract: Abstract. Two cytoplasmic variants of the or6 integrin, ot6A and t~6B, have been identified previously (Hogervorst, E,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
83
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(94 citation statements)
references
References 53 publications
10
83
1
Order By: Relevance
“…It has been demonstrated that the a6pl integrin is of major importance in the transformation of the metanephric mesenchyme into epithelium during early kidney morphogenesis (Sorokin et al, 1990). Since only a6B is detected in adult kidney as well Hogervorst et al, 1993) it could be another example of an exclusive expression of a6B during development, although a more detailed study of kidney morphogenesis needs to be performed before the presence of a6A can be excluded.…”
Section: Only A6b Is Expressed In Several Embryonic Organs and Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the a6pl integrin is of major importance in the transformation of the metanephric mesenchyme into epithelium during early kidney morphogenesis (Sorokin et al, 1990). Since only a6B is detected in adult kidney as well Hogervorst et al, 1993) it could be another example of an exclusive expression of a6B during development, although a more detailed study of kidney morphogenesis needs to be performed before the presence of a6A can be excluded.…”
Section: Only A6b Is Expressed In Several Embryonic Organs and Tissuesmentioning
confidence: 99%
“…A functional difference between these two splice variants during embryonic development has not yet been directly demonstrated. However, the fact that a6B is already expressed in preimplantation mouse embryos and a6A for the first time in implanting embryos (Hierck et al, 1993;Sutherland et al, 1993), and the observation that the two splice variants have a different, although sometimes overlapping, expressionldistribution in adult murine and human tissues Hogervorst et al, 1993) and in the developing chick retina (de Curtis and Reichardt, 1993) strongly suggest that their functions may not be identical. Support for this notion is provided by studies on cells transfected with chimeric a integrin subunits, i.e., subunits containing the extracellular domain of one a subunit and the cytoplasmic domain of another.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 4A, tein is weaker than that of {34A. We also tested the ability of the GST-,B4 fusion proteins to associate with proteins from another cell line, the human UMSCC-22B line, which contains hemidesmosome-like structures (Hogervorst et al, 1993). Both GST-cyto,B4A and GST-cyto,34B precipitated a protein of 500-kDa that comigrated with HD1 from these cells as well ( Figure 4B), and again the affinity of cyto,f4B for this protein appeared to be lower than that of cytof34A.…”
Section: Generation Of Gst-g84 Fusion Proteinsmentioning
confidence: 99%
“…For immunofluorescence analysis of ␣3 and ␣6 integrins, CAC2 cells were cultured on SIKVAV and IVSKVA for 4 hours and subjected to the immunofluorescence protocol described by Hogervorst et al 35 Cells were fixed in 1% paraformaldehyde in PBS for 10 minutes, rinsed, permeabilized with 0.5% Triton X-100 (Sigma) in PBS for 5 minutes, and blocked with 1% BSA for 30 minutes. Samples were then double-labeled with antibodies against ␣3 (mAb, clone P1B5; Chemicon) and ␣6 (rat mAb, clone GoH3; Chemicon) integrins diluted 1:100 in PBS for 1 hour.…”
Section: Immunofluorescencementioning
confidence: 99%